An exploratory study of Chinese tourists’ expectations and preferences of New Zealand as a travel destination - Long, Hailu (Auckland University of Technology, 2012)
This research explores the Chinese tourists’ expectations and preferences on overseas group tours. It highlights the value of customer expectations and preferences in destination planning for the Chinese outbound market and the importance of visitors’ knowledge in facilitating marketing strategies. In particular, the basis of this research is to demonstrate the application of customer expectation theories in industry practice. In order to develop greater insight into the Chinese tourist market, the key focus of this study is to develop an applied model of Chinese tourist preferences and expectations of New Zealand as a tour destination. The research uses a quantitative method to determine Chinese tourist expectations and preferences in New Zealand group tours. A questionnaire survey was used for data collection. With limited resources of time and money, a convenient sample of 100 Chinese tourists was drawn from Chinese visitors who were travelling in group tours in New Zealand in February and March 2012. The survey identified the general travel expectations and preferences of Chinese tourists on New Zealand group tours in five areas: accommodation, dining, activity, tour guide and itinerary. The findings offered particular evidence for improving service quality from the service providers, as complaints about tour guides showed up as a common cause of dissatisfaction in the survey. In addition, this research emphasized that culture is a key factor in building Chinese tourists’ expectations and preferences. To date there are limited studies conducted to investigate Chinese tourists’ expectations and preferences for New Zealand as a destination, even though this is increasing. Understanding the Chinese tourists’ preferences and expectations is the first step for delivering quality service and providing better visitor experiences. Thus, this study emphasizes not only the importance of tourist expectations and preferences in delivering superior service, but also the need for more research in this area for empirical and theoretical advancement.
Keywords: Chinese tourists; Expectation; Preference; New Zealand group tour; ADS